The Francisella Intracellular Life Cycle: Toward Molecular Mechanisms of Intracellular Survival and Proliferation - Chong, Audrey; Celli, Jean (Frontiers in Microbiology, 2010)
The tularemia-causing bacterium Francisella tularensis is a facultative intracellular organism with a complex intracellular lifecycle that ensures its survival and proliferation in a variety of mammalian cell types, including professional phagocytes. Because this cycle is essential to Francisella pathogenesis and virulence, much research has focused on deciphering the mechanisms of its intracellular survival and replication and characterizing both bacterial and host determinants of the bacterium's intracellular cycle. Studies of various strains and host cell models have led to the consensual paradigm of Francisella as a cytosolic pathogen, but also to some controversy about its intracellular cycle. In this review, we will detail major findings that have advanced our knowledge of Francisella intracellular survival strategies and also attempt to reconcile discrepancies that exist in our molecular understanding of the Francisella–phagocyte interactions.